CATANA: an online modelling environment for proteins and nucleic acid nanostructures - Kuťák, David; Melo, Lucas; Schroeder, Fabian; Jelic-Matošević, Zoe; Mutter, Natalie; Bertoša, Branimir; Barišić, Ivan (Nucleic acids research, 2022)
In the last decade, significant advances have been made towards the rational design of proteins, DNA, and other organic nanostructures. The emerging possibility to precisely engineer molecular structures resulted in a wide range of new applications in fields such as biotechnology or medicine. The complexity and size of the artificial molecular systems as well as the number of interactions are greatly increasing and are manifesting the need for computational design support. In addition, a new generation of AI-based structure prediction tools provides researchers with completely new possibilities to generate recombinant proteins and functionalized DNA nanostructures. In this study, we present Catana, a web-based modelling environment suited for proteins and DNA nanostructures. User-friendly features were developed to create and modify recombinant fusion proteins, predict protein structures based on the amino acid sequence, and manipulate DNA origami structures. Moreover, Catana was jointly developed with the novel Unified Nanotechnology Format (UNF). Therefore, it employs a state-of-the-art coarse-grained data model, that is compatible with other established and upcoming applications. A particular focus was put on an effortless data export to allow even inexperienced users to perform in silico evaluations of their designs by means of molecular dynamics simulations. Catana is freely available at http://catana.ait.ac.at/.
Keywords: nanostruktury; Nucleic Acids; DNA; Nucleic Acid Conformation; nanotechnologie; nukleové kyseliny; Nanotechnology; Recombinant Fusion Proteins; Nanostructures; konformace nukleové kyseliny; rekombinantní fúzní proteiny